Galong dan Pathet Manyura dalam Pedalangan Ngayogyakarta: sebuah Perbandingan “Rasa” - Aris - Wahyudi (Institut Seni Indonesia Yogyakarta, 2021)
Galong is a unique and interesting phenomenon in the world of paddling. His capacity as a pathet is still a debate today. Some groups say that Galong is its own pathet, while others say Galong is part of the Manyura pathet. The debate arose because his presence in the puppet show was in Manyura's pathet, but he had a distinctive and relatively prominent five tone. As a result, Galong has a different musical feel to Manyura's pathet. On the other hand, tone five is the dominant tone in sanga pathet and becomes a abstinence in Pathet Manyura. Based on the pathet philosophy, I assume that the pathet in pedalangan and karawitan is only divided from three, namely Nem, Sanga, and Manyura. Therefore Galong capacity needs to be reviewed in relation to puppet shows. To that, the question is: 1) how does Playon Galong